A influência dos serviços de fretes terceirizados na competitividade de lojas virtuais no estado do Paraná - Francisco, Luciano Furtado Corrêa (2025)
Outsourcing delivery services has become a widespread practice among small and medium-sized online retailers, especially given the challenges of maintaining proprietary logistics structures. This dissertation investigates how third-party freight services influence the competitiveness of e-commerce operations in the state of Paraná, focusing on both operational aspects and the relational dynamics between retailers and third-party transporters. The study gains relevance from the scarcity of research addressing this topic through a regional and qualitative lens. To fulfill its objectives, the research employed Content Analysis, based on semi-structured interviews with ten online store managers and five representatives of transportation companies operating in Paraná. The data revealed eleven thematic categories, showing that retailer–carrier relationships are marked by decision-making asymmetries, contractual fragility, and limited integration. These factors undermine delivery efficiency and negatively impact customer perception. The findings suggest that the competitiveness of online retailers is closely tied to the maturity of their relationships with logistics providers, their capacity for collaborative innovation, and the perceptions shaped by the different actors involved, highlighting the need for more balanced and transparent models of partnership.